PENGARUH DER, FIRM SIZE, CR, DAN WCTO TERHADAP ROA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2016-2018 - Dewa Ayu Nyoman Yogi Linggasari; Komang Fridagustina Adnantara (Universitas Triatma Mulya, 2020)
This study aims to determine the effect of Debt to Equity Ratio (DER), Firm Size, Current Ratio (CR), and Working Capital Turn Over (WCTO) on Return on Assets (ROA) of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The period of this research is 2016-2018. The study population includes all Manufacturing Companies listed on the Indonesia Stock Exchange during 2016- 2018. The sample selection technique uses a purposive sampling method and data obtained by 47 companies. The data analysis method used is multiple linear regression analysis. The results of this study indicate the Debt to Equity Ratio (DER) has a negative and significant effect on Return On Assets (ROA). Firm Size, Current Ratio (CR), and Working Capital Turn Over (WCTO) have a positive and significant effect on Return On Assets (ROA). Adjusted R Square value of 0.447 means that 44.7% of the Return On Assets (ROA) variable is influenced by Debt to Equity Ratio (DER), Firm Size, Current Ratio (CR), and Working Capital Turn Over (WCTO) variables, while the remaining 55.3% is influenced by other factors not examined in this study.